(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article covers the scientific, theoretical and practical foundations of the formation of environmental knowledge, skills and attitudes in the process of teaching the subject "Education" to primary school students. The article analyzes the goals and objectives of modern environmental education, the pedagogical conditions for the formation of a responsible attitude towards nature in students, as well as the mechanisms for developing environmental awareness through the content of the subject "Education". The study developed ways to form an ecological culture in primary school students based on effective mechanisms such as an integrative approach to the educational process, interactive methods, the use of media, and the establishment of project and observation activities. The article also analyzes the pedagogical foundations of assimilating environmental knowledge in a manner appropriate to the age-related psychological characteristics of students, the motivational and cognitive components of environmental education. As a result, it is scientifically substantiated that in the modern model of the subject "Education" it is possible to improve the systematic mechanisms for the formation of environmental knowledge, and to deepen the environmental awareness of students by enriching the content and methods of education.